Patterns of alcohol and drug utilization in trauma patients during the COVID-19 pandemic at six trauma centers - Constance McGraw; Kristin Salottolo; Matthew Carrick; Mark Lieser; Robert Madayag; Gina Berg; Kaysie Banton; David Hamilton; David Bar-Or (BMC, 2021)
Abstract Background Since the national stay-at-home order for COVID-19 was implemented, clinicians and public health authorities worldwide have expressed growing concern about the potential repercussions of drug and alcohol use due to social restrictions. We explored the impact of the national stay-at-home orders on alcohol or drug use and screenings among trauma admissions. Methods This was a retrospective cohort study at six Level I trauma centers across four states. Patients admitted during the period after the onset of the COVID-19 restrictions (defined as March 16, 2020-May 31, 2020) were compared with those admitted during the same time period in 2019. We compared 1) rate of urine drug screens and blood alcohol screens; 2) rate of positivity for drugs or alcohol (blood alcohol concentration ≥ 10 mg/dL); 3) characteristics of patients who were positive for drug or alcohol, by period using chi-squared tests or Fisher's exact tests, as appropriate. Two-tailed tests with an alpha of p < 0.05 was used on all tests. Results There were 4762 trauma admissions across the study period; 2602 (55%) in 2019 and 2160 (45%) in 2020. From 2019 to 2020, there were statistically significant increases in alcohol screens (34% vs. 37%, p = 0.03) and drug screens (21% vs. 26%, p < 0.001). Overall, the rate of alcohol positive patients significantly increased from 2019 to 2020 (32% vs. 39%, p = 0.007), while the rate of drug positive patients was unchanged (57% vs. 52%, p = 0.13). Of the 1025 (22%) patients who were positive for alcohol or drugs, there were significant increases in a history of alcoholism (41% vs. 26%, p < 0.001), and substance abuse (11% vs. 23%, p < 0.001) in the 2020 period. No other statistically significant differences were identified among alcohol or drug positive patients during COVID-19 compared to the same period in 2019. Conclusions Our first wave of COVID-19 data suggests that trauma centers were admitting significantly more patients who were alcohol positive, as well those with substance use disorders, potentially due to the impact of social restrictions and guidelines. Further longitudinal research is warranted to assess the alcohol and drug positive rates of trauma patients over the COVID-19 pandemic.